ANALISIS PENERAPAN PENGENDALIAN INTERNAL PERSEDIAAN DALAM PENGELOLAAN PERSEDIAAN BARANG DAGANG (Studi Kasus Pada Minimarket Indomaret PT. Indomarco Prismatama) - Safitri, Ariska; Nasution, M. Irsan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The purpose of this study is to determine the internal control system for merchandise inventory at Indomaret Minimarket. The problem that occurs in this company is the frequent loss of inventory. Therefore, this study aims to determine the procedures for receiving, issuing goods and evaluating the internal control system for inventory accounting at Indomaret. This type of research is descriptive research. The research method used is a qualitative descriptive method. Data collection was carried out by interview and documentation. Data sources use primary data and secondary data. The results of this study are that the internal control system for merchandise inventory at Indomaret Minimarket has not been implemented properly. Effective actions to minimize damage and loss of merchandise and maintain inventory levels have not been implemented properly. The internal control system implemented by the company has not been running effectively and efficiently because there are several elements of internal control that have not been running well, such as the absence of strict separation of stores, store functions and warehouse functions and goods inspection transactions. implemented by only one function. In addition, there has been no regular employee rotation, in the Indomaret warehouse and store there are still several CCTV cameras whose cameras are blurry or even dead and there is also no monitoring function that aims to monitor consumers who shop at Indomaret stores so that they do not rotate employees regularly to be able to anticipate theft and the like.